Developing Teachers Digital Competence Through International STEM Coding Training - Maharani, Siti Dewi; Hartono, Hartono; Syarifuddin, Syarifuddin; Inderawati, Rita; Santri, Didi Jaya (Pascasarjana Universitas Mataram, 2024)
The purpose of this Community Service is to enhance the digital skill of teachers with coding training in STEM in the city of Palembang. Sriwijaya University is organizing this community service in collaboration with ARtec Japan and Indonesian STEM Association for the benefit of. There are 46 participating teachers attending this event, coming from different levels of education: SD, SMP, dan SMA (primary and secondary school). After the community service activities, a significant improvement was noted in the participants' understanding and technical skills on how to use coding in the classroom. This is evidenced by increased posttest scores across all elements in the provided evaluation instrument with a mean increase of 28 points. The approaches used in this training are lectures, practical training, and mentoring. In conclusion, what can be done from this training is that well-organized STEM Coding Training has boosted digital literacy, technical skills, and the confidence of instructors themselves